Fitness effects of blaCTX-M-15-harbouring F2:A1:B− plasmids on their native Escherichia coli ST131 H30Rx hosts. (26th July 2022) - Palkovicova, Jana; Sukkar, Iva; Delafuente, Javier; Valcek, Adam; Medvecky, Matej; Jamborova, Ivana; Bitar, Ibrahim; Phan, Minh-Duy; San Millan, Alvaro; Dolejska, Monika
Abstract: Objectives: To investigate the fitness effects of large bla CTX-M-15 -harbouring F2:A1:B− plasmids on their native Escherichia coli ST131 H 30Rx hosts. Methods: We selected five E. coli ST131 H 30Rx isolates of diverse origin, each carrying an F2:A1:B− plasmid with the bla CTX-M-15 gene. The plasmid was eliminated from each isolate by displacement using an incompatible curing plasmid, pMDP5_cureEC958. WGS was performed to obtain complete chromosome and plasmid sequences of original isolates and to detect chromosomal mutations in 'cured' clones. High-throughput competition assays were conducted to determine the relative fitness of cured clones compared with the corresponding original isolates. Results: We were able to successfully eliminate the F2:A1:B− plasmids from all five original isolates using pMDP5_cureEC958. The F2:A1:B− plasmids produced non-significant fitness effects in three isolates and moderate reductions in relative fitness (3%–4%) in the two remaining isolates. Conclusions: We conclude that F2:A1:B− plasmids pose low fitness costs in their E. coli ST131 H 30Rx hosts. This plasmid-host fitness compatibility is likely to promote the maintenance of antibiotic resistance in this clinically important E. coli lineage.